Comunicação : a hermenêutica das formas simbólicas na Revista Realidade - Silveira, Bruna Teixeira da (2013)
In the presente work, we will perform an assey regarding to the symbolic forms of the Magazine Reality, which has circulated in Brazil from 1966 to 1976. During these ten years, it became a reference to the journalist class, inovating with its diagramation and melding, in a coherent way, reports and photographs. With montlhy periodicity, the Reality put in argument tabu issues for the period of its currency, that being, the military dictarship. Therefore, the corpus of work chosen by us chomprehends five Reports, published during these media s ten years of life. Being them: Separation or Divorce, published in 1966; A Dispatch of Love, from the same year; I was a Simple Worker, from 1967; They Want to Take the Government Down, from 1968; and Chico puts our Music in Order, from 1972. This way, our proposal aimes to understand the Sense s Dramatization through Photography and the union of this one with the Reality s speech, taking into account the creation of the textual and photographic stereotypes, as well as the mythological forms created by the writing , capturing the emission of Culture from the Report s carachteres, the magazine and the state and from the existing power conflicts between the govern people and the civilian, from the presence of the encratic and non-encratic social dialects that compose the narrative presented in the analized pages, making us comprehend the strugle of a generation made silent by the censorship, mystified by the Media, which on the other hand, suffered from the halter of the Repression Organs